PENGARUH PRODUCT QUALITY, WORD-OF MOUTH ,PRODUCT PACKAGING, DAN BRAND IMAGE TERHADAP CONSUMER SATISFACTION MELALUI PURCHASE DECISION SEBAGAI VARIABLE INTERVENING PADA PRODUK AMDK MEREK AIR SYIFA’ P2S2 DI PONPES SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Abdul Awal; Yudha Praja; Rini Kartika Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to determine the effect of Product quality, Word of mouth, Product packaging, and Brand Image on Consumer satisfaction Through Purchase decision as Intervening Variables in Syifa' P2S2 Brand Bottled Drinking Water Products at Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo. The sampling technique in this study used non-probability sampling with a purposive sampling approach, involving 115 respondents. The data analysis tool used in this study was smart PLS 3.0. The data analysis methods used in this study include convergent validity, reliability, classical assumption testing, goodness of fit (GOF) testing, coefficient of determination testing, structural equation analysis (inner model), and hypothesis testing. The direct effect hypothesis test results indicate that product quality has a positive and significant effect on purchase decisions. Word of mouth has a positive but insignificant effect on purchase decisions. Product packaging and brand image have a positive and significant effect on purchase decisions. Product quality and product packaging have a negative but insignificant effect on consumer satisfaction. Word of mouth has a positive but insignificant effect on consumer satisfaction. Brand image and purchase decisions have a positive and significant effect on consumer satisfaction. The indirect effect hypothesis test results indicate that product quality, product packaging, and brand image have a positive and significant effect on consumer satisfaction through purchase decisions. Word of mouth has a positive but insignificant effect on consumer satisfaction through purchase decisions.